Peta Pemikiran Fiqh Pasca Madzhab - Tobibatussaadah Tobibatussaadah (Postgraduate State Islamic Institute (IAIN) Metro, 2020)
The period of the development of madzhab experienced ups and downs, during its golden age the scientific development in heretical fiqh was very rapid, the scales of mujtahid mutlaq were in the golden age. After generalization of the school of Islamic legal thought has stagnated, this attitude can be seen from the behavior of Muslims after the school of Nostalgia in the past and the assumption that the established school of thought has crystallized in Muslims in that period. This research is a literature study that will explore the post-madzhab thought map of fiqh. The result of the research is that the development of fiqh thought has stagnated, which occurs only by practicing taqlid to the existing schools of thought, and the cultural errors of syarah and hasyiyah. They no longer try to solve the prolematics of their time based on existing realities. So that the teachings of Islam are only limited to theory and ritual, not applicable as positive law for its people in all aspects of life.